2021
DOI: 10.24198/prh.v6i1.32112
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan media sosial dalam membangun reputasi anggota legislatif di Jawa Barat

Abstract: Pada masa pandemi COVID-19 diperlukan optimalisasi penggunaan media komunikasi seperti sosial media oleh pemerintah, termasuk para anggota lembaga legislatif, baik di pusat maupun daerah. Padahal kegiatan ini bisa saja dilakukan dengan menggunakan sosial media dan tidak terdapat resiko dalam pelaksanaan komunikasi pada masa reses. Namun, masih terdapat keterbatasan penggunaan media komunikasi virtual yaitu sosial media oleh lembaga legislatif. Tujuan dari penelitian ini adalah untuk menyelidiki penggunaan sosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
1
2
0
5
Order By: Relevance
“…But content related to the publication of the activities of top police officials can be something that makes the public not feel "connected" to police accounts. Several previous studies have shown that social media can be one of the channels to form a positive self-image (Sjoraida et al, 2021;Mulyani, 2021). The imagery in the two journals above uses their social media accounts.…”
Section: Resultsmentioning
confidence: 99%
“…But content related to the publication of the activities of top police officials can be something that makes the public not feel "connected" to police accounts. Several previous studies have shown that social media can be one of the channels to form a positive self-image (Sjoraida et al, 2021;Mulyani, 2021). The imagery in the two journals above uses their social media accounts.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are areas of work that they must do remotely during this pandemic, such as meeting residents to absorb aspirations, meetings between institutions, or working visits to other institutions. Legislators are closely related to political communication activities, which in this new normal era should be able to adjust the form of virtual communication and use technology to carry out political communication (Sjoraida et al, 2021).…”
Section: Discussion: Theoretical and Practical Implicationmentioning
confidence: 99%
“…Media sosial di memungkinkan audiens untuk memiliki akses yang lebih mudah ke informasi yang lebih baik tentang peristiwa terkini, kebijakan atau program, meningkatkan persepsi mereka tentang transparansi dalam pemerintahan. Penggunaan media sosial oleh mendapatkan informasi yang lebih baik karena tahap awal penggunaan media sosial di pberfokus pada transparansi data untuk meningkatkan kesadaran publik terhadap data dan proses pemerintahan (Sjoraida, 2021).…”
Section: Gambar 2 Data Hasil Survey Mbkmunclassified